Effect of an Interplanetary Coronal Mass Ejection on Saturn’s Radio Emission - Cecconi, B.; Witasse, O.; Jackman, C. M.; Sánchez-Cano, B.; Mays, M. L. (Frontiers in Astronomy and Space Sciences, 2022)
The Saturn Kilometric Radiation (SKR) was observed for the first time during the flyby of Saturn by the Voyager spacecraft in 1980. These radio emissions, in the range of a few kHz to 1 MHz, are emitted by electrons travelling around auroral magnetic field lines. Their study is useful to understand the variability of a magnetosphere and its coupling with the solar wind. Previous studies have shown a strong correlation between the solar wind pressure and the SKR intensity. However, up to now, the effect of an Interplanetary Coronal Mass Ejection (ICME) has never been examined in detail, due to the lack of SKR observations at the time when an ICME can be tracked and its different parts be clearly identified. In this study, we take advantage of a large ICME that reached Saturn mid-November 2014 (Witasse et al, 2017). At that time, the Cassini spacecraft was fortunately travelling within the solar wind for a few days, and provided a very accurate timing of the ICME structure. A survey of the Cassini data for the same period indicated a significant increase in the SKR emissions, showing a good correlation after the passage of the ICME shock with a delay of ~13 hours and after the magnetic cloud passage with a delay of 25-42 hours. In between, a smaller SKR burst could be correlated with a proton flux peak occurring during the passage of the ejecta of the ICME.